THE EFFECTIVENESS OF CLIL TECHNOLOGY AND ITS POTENTIAL FOR IMPLEMENTATION IN HIGHER EDUCATION (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the theoretical and practical aspects of CLIL (Content and Language Integrated Learning) educational technology, its effectiveness in higher education, and the possibilities of its implementation in the education system of Uzbekistan. Based on international and local research, the article highlights the advantages and challenges of CLIL and provides practical recommendations.